Environmental health and diarrhic diseases: socioeconomic, environmental and sanitary indicators in an amazonian municipality (Research, Society and Development, 2020)
In recent decades, the impacts of environmental problems on the socioeconomic issues of populations have been the subject of debates about infectious outbreaks, such as diarrhea and diseases related to inadequate environmental sanitation - DRSAI. The aim of this paper is to discuss the socio-environmental determination processes in Curionópolis - PA, an Amazonian municipality, based on the analysis of socioeconomic, environmental and health indicators between the years 2015-2019. The following data were used: Gross Domestic Product-GDP, GDP per capita, population estimate, population growth rate, cases and admissions of DDA and DRSAI per year. Census data from 1991, 2000 and 2010 referring to the Municipal Human Development Index-MHDI, Gini Index, coverage of the water supply network, the sewage system-SES and garbage collection were used. The survey revealed high municipal economic rates. However, the population is exposed to problems resulting from the constant gap in basic sanitation and sewage coverage, in addition to unsatisfactory public health services, showing the socio-environmental vulnerability in the municipality.